2018
DOI: 10.1037/pas0000461
|View full text |Cite
|
Sign up to set email alerts
|

Measures of body image: Confirmatory factor analysis and association with disordered eating.

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 54 publications
(152 reference statements)
3
40
1
Order By: Relevance
“…Two studies (respectively) reported a significant positive correlation between body checking and drive for thinness (Alperin et al, ; Chang, ), bulimic behaviours (Chang, ; Dakanalis et al, ), and the total score of the EAT‐26 (De Berardis et al, ; Engle, ). Three studies reported a positive association between body checking and body dissatisfaction (Chang, ; Pellizzer, Tiggemann, Waller, & Wade, ; Vartanian & Grisham, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies (respectively) reported a significant positive correlation between body checking and drive for thinness (Alperin et al, ; Chang, ), bulimic behaviours (Chang, ; Dakanalis et al, ), and the total score of the EAT‐26 (De Berardis et al, ; Engle, ). Three studies reported a positive association between body checking and body dissatisfaction (Chang, ; Pellizzer, Tiggemann, Waller, & Wade, ; Vartanian & Grisham, ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, one study (Jansen et al, ) found no significant association between body avoidance and the EDE‐Q. Two studies reported significant positive correlations between body avoidance and body dissatisfaction (Carmona et al, ; Pellizzer et al, ), and two studies reported a significant positive correlation between body avoidance and the total score of the EAT‐26 (Engle, ; Rodgers, Melioli, Laconi, Bui, & Chabrol, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate greater BIF. It has strong psychometric properties (see Pellizzer, Tiggemann, Waller, & Wade, ). Internal consistency in the current study was .92.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate greater body checking. Psychometric properties vary across studies (see Pellizzer et al, 2017).…”
Section: Body Checkingmentioning
confidence: 99%